TASYBIH DALAM ALQURAN: ANALISIS TASYBIH PADA SEGI RUKUN DALAM SURAT YUSUF - Oktavia, Yola; Wardani, Rita Wilda; Muassomah, Muassomah; Muzakki, Akhmad (Hijai - Journal on Arabic Language and Literature, 2023)
ABSTRACT tasybih is part of the science of Balaghah. Tasybih is included in Bayan science which is a technique of explaining a meaning and suggestions for explaining a trait. This study aims for this study aims to (1) describe the forms of tasybih contained in Yusuf's letter, and (2) describe the faidah tasybih contained in Yusuf's letter. The results of the research that the researchers found in this study were: there was one verse from each tasybih in terms of the pillars in Yusuf's letter, namely tasybih mursal, mujmal, muakad, and baligh. By expressing each tasybih that is different and can be analyzed with the expression of tasybih. Based on the object or thing that is likened, sometimes tasybih becomes an affirmation, and sometimes tasybih has the intention to beautify something or to praise something. Â  ABSTRAK tasybih merupakan bagian dari ilmu Balaghah. Tasybih merupakan kajian ilmu Bayan yang menjelaskan sebuah makna dan mensifati makna tersebut. Penelitian ini bertujuan untuk (1) memaparkan bentuk-bentuk tasybih yang ada pada surat Yusuf, dan (2) mendeskripsikan faidah tasybih yang terkandung dalam surat Yusuf. Adapun hasil penelitian yang peneliti temukan pada penelitian ini ialah: terdapat satu ayat dari masing-masing tasybih dari segi rukun dalam surat Yusuf yakni tasybih mursal, mujmal, muakad, dan baligh. Dengan mengungkapkan masing-masing tasybih yang berbeda-beda dan dapat dianalisis dengan ungkapan tasybih. Berdasarkan benda atau hal yang diserupakan adakalanya tasybih menjadi penegasan, dan adakalanya tasybih memiliki maksud memperindah sesuatu maupun memuji sesuatu.